(untitled) (Fiep Bulletin - online, 2017)
This research aims to create an instruction model for the optimization of teaching football to fifth graders of the sports high-school of Bacau, Romania. Starting with the academic year 1999-2000, a National System for the School Physical Education Assessment was introduced in the primary, middle school, high school, and higher education. Considering these, this research proposes new teaching strategies that would include relay races using the football, the assessment of these strategies being made according to the middle school final performance standards foreseen in the curriculum.Relay races are increasingly used as action means during the middle school physical education lessons, due to the fact that they are attractive to children, both as play during their leisure time, and as organized games during the physical education lesson. The use of relay races with the football during the physical education lesson has certain tendencies that influence directly the development of the main motor skills and moral-volitional qualities.Three challenges were selected for the final testing, chosen from the ones established in the National System for the School Physical Education Assessment: 25 m sprint, 5x5 m relay, and standing long jump.At the end of the research, the initial hypothesis was confirmed: The correct management of the teaching-learning process, by introducing relay races using the football in the content of the sports high-school physical education lesson, leads to the accomplishment of the standards established for certain evaluation challenges by the Ministry of Education, Research, Youth and Sports through its National System for the School Physical Education Assessment.